Populism in the Communication Strategy of Lula and Bolsonaro: An Analysis of the Television Debates in Brazil’s 2022 General Election - Francisco-Sérgio Lima-de-Sousa; Pablo Gómez-Iniesta; José-María Herranz-de-la-Casa (Communication & Society (Formerly Comunicación y Sociedad), 2023)
The 2022 presidential election in Brazil involved two radically different candidates but with broad similarities in their populist discourse and communication strategies. The electoral campaign and the results polarized the country between the supporters of the outgoing president, Jair Bolsonaro, and the incoming one, Lula da Silva. This article analyzes the two television debates that took place in the second round of the presidential election in October. The interventions of the candidates have been studied using the methodology of critical discourse analysis applied by Hawkins (2010). The goal is to discover the degree of populism present in the candidates’ discourse in the two debates studied. The results show evidence of the highly populist nature of the discourse of the two leaders in both television events. This characteristic, as well as other important aspects of the campaigns and the narrow margin of Lula’s eventual victory, may explain the level of polarization evident in the country. It may also be the reason behind the rejection of the election results by the followers of Bolsonaro and their protest against the change in president.